2004
DOI: 10.1101/lm.69704
|View full text |Cite
|
Sign up to set email alerts
|

Perirhinal Cortex Muscarinic Receptor Blockade Impairs Taste Recognition Memory Formation

Abstract: The relevance of perirhinal cortical cholinergic and glutamatergic neurotransmission for taste recognition memory and learned taste aversion was assessed by microinfusions of muscarinic (scopolamine), NMDA (AP-5), and AMPA (NBQX) receptor antagonists. Infusions of scopolamine, but not AP5 or NBQX, prevented the consolidation of taste recognition memory using attenuation of neophobia as an index. In addition, learned taste aversion in both shortand long-term memory tests was exclusively impaired by scopolamine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 56 publications
(77 reference statements)
2
15
1
Order By: Relevance
“…Indeed, local infusion of scopolamine in the perirhinal cortex or cholinergic deafferentation of the rhinal cortices produce deficits in tasks probing various types of memory (Warburton et al, 2003;Abe et al, 2004;Gutierrez et al, 2004;McGaughy et al, 2005;Turchi et al, 2005;Winters and Bussey, 2005). Although it was proposed that muscarinic receptor activation regulates rhinal contributions to memory by modulating synaptic plasticity in the rhinal cortices (Warburton et al, 2003), the results of the present study suggest that an additional mechanism might be at play.…”
Section: Cholinergic Control Of Long-range Inhibition In the Rhinal Ccontrasting
confidence: 44%
See 2 more Smart Citations
“…Indeed, local infusion of scopolamine in the perirhinal cortex or cholinergic deafferentation of the rhinal cortices produce deficits in tasks probing various types of memory (Warburton et al, 2003;Abe et al, 2004;Gutierrez et al, 2004;McGaughy et al, 2005;Turchi et al, 2005;Winters and Bussey, 2005). Although it was proposed that muscarinic receptor activation regulates rhinal contributions to memory by modulating synaptic plasticity in the rhinal cortices (Warburton et al, 2003), the results of the present study suggest that an additional mechanism might be at play.…”
Section: Cholinergic Control Of Long-range Inhibition In the Rhinal Ccontrasting
confidence: 44%
“…Having established that the perirhinal cortex contains GABAergic neurons projecting to the vlEC, we turned our attention to the modulation of this long-range inhibition by acetylcholine because previous work revealed that the memory functions of the perirhinal cortex require muscarinic receptor activation (Warburton et al, 2003;Abe et al, 2004;Gutierrez et al, 2004). Acetylcholine is known to exert various effects on inhibition, the most common of which is to presynaptically inhibit GABA release via muscarinic receptors (Ben-Ari et al, 1981; Behrends and ten Bruggencate, 1993) (for review, see Miller, 1998).…”
Section: Regulation Of Long-range Gabaergic Inhibition By Acetylcholinementioning
confidence: 99%
See 1 more Smart Citation
“…However, in humans, the maximally tolerated dose of the AMPA/kainate antagonist LY293538 did not disrupt cognitive function (Sang et al 1998). In addition, behavioral studies and LTP studies that have used antagonists with greater selectivity for AMPARs than kainate receptors have not consistently found learning-related memory impairments or deficits in LTP (Parada et al 1992; for review of AMPARs and learning, see Danysz et al 1995;Misztal and Danysz 1995;Sato et al 1995;Stephens and Cole 1996;Li et al 1997;Lu and Wehner 1997;Filliat et al 1998;Mead and Stephens 1999;Kapus et al 2000;Lees 2000;Aultman and Moghaddam 2001;Pitsikas et al 2002;Willmore et al 2002;Gutierrez et al 2004). For example, Lu and Wehner (1997) found that in C57BL/6 mice, cued and contextual fear conditioning was insensitive to the AMPAR antagonist NBQX at a dose three times higher than a dose of NBQX that produced 100% protection against audiogenic seizures in mice (Swedberg et al 1995).…”
mentioning
confidence: 99%
“…IC lesions appear to produce no effects on animals' capacity to attain taste familiarity [151], but several reports document a role for the IC in taste familiarity learning as a result of pharmacological manipulations [153,154], showing that taste familiarity requires cholinergic activity in the IC [155,156] but that it is independent of NMDA and AMPA channel activity [157][158][159][160]. Perhaps this dichotomy can be explained either by compensation from other areas after IC lesions or, given the role of neophobia discussed above, it is possible that IC output per se may modulate familiarity.…”
Section: Role Of the Ic In Taste Functionmentioning
confidence: 99%